PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN BERBANTU APLIKASI CABRI 3D V2 TERHADAP PEMAHAMAN KONSEP KUBUS DAN BALOK KELAS VIII SMPIT INSAN MULIA - Fhela Vhantoria Ningrum; Karsoni Bertadinata; Muhammad Rafi Sundarta (Universitas Muhammadiyah Kotabumi, 2023)
The lack of use of learning media to illustrate abstract forms into concrete forms, makes students less understanding of the concepts in cube and block material. This study aims to develop learning media with the help of the Cabri 3D v2 application for understanding concepts in the material of cubes and blocks for class VIII SMP. This study uses the development method belonging to Sugiyono (2017), this research limits its stages only to stage 5, namely until the product revision stage I. After conducting research and development of Cabri 3D v2 assisted learning media, the results are as follows: 1) material experts get percentages 86.66% in the